DOI: 10.3990/1.9789036553414
|View full text |Cite
|
Sign up to set email alerts
|

Over the dike top: modelling the hydraulic load of overtopping waves including transitions for dike cover erosion

Abstract: Samenvatting 1 Introduction 2 An analytical model of wave overtopping flow velocities on dike crests and landward slopes 3 Modelling the wave overtopping flow over the crest and the landward slope of grass-covered flood defences. 4 The wave overtopping load on landward slopes of grasscovered flood defences: deriving practical formulations using a numerical model. 5 The effects of transitions in cover type and height on the wave overtopping load on grass-covered flood defences 6 The cross-dike failure probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 142 publications
(538 reference statements)
0
4
0
Order By: Relevance
“…In reality, the bed roughness changes for clay in erosion holes and asphalt for roads. However, previous studies have shown that the change in roughness only has a limited effect on the hydraulic load (Van Bergeijk, 2022;Van Bergeijk et al, 2020b;Bomers et al, 2018).…”
Section: Numerical Model Set-upmentioning
confidence: 94%
See 1 more Smart Citation
“…In reality, the bed roughness changes for clay in erosion holes and asphalt for roads. However, previous studies have shown that the change in roughness only has a limited effect on the hydraulic load (Van Bergeijk, 2022;Van Bergeijk et al, 2020b;Bomers et al, 2018).…”
Section: Numerical Model Set-upmentioning
confidence: 94%
“…A model study is performed wherein the main design parameters are varied. The effect of the design parameters on the load are quantified using a regression analysis as described by Chen et al (2020) and Van Bergeijk et al (2022). For all four cases, the overtopping volume V is varied since this parameter determined the amount of water flowing over the crest.…”
Section: The Hydraulic Load At Transitionsmentioning
confidence: 99%
“…Another way of dealing with this is to remove the air phase from the VoF implementation. This is the approach used by García-Maribona et al (2021, 2022, which also explains the lack of air under broken bores in their results. This was until recently not available in OpenFOAM, however, a novel study has implemented such a model in the OpenFOAM environment (Qwist and Christensen, 2023).…”
Section: Alternative Methodsmentioning
confidence: 93%
“…This model uses the Volume of Fluid (VoF) method to discriminate between air and water in the solution. Recently, a different model based on the IH2VOF model was used to study morphodynamics and intraswash suspended sediment dynamics under bichromatic waves (García-Maribona et al, 2021, 2022. An important difference between these two studies and the studies by Li et al (2019) and Kranenborg et al (2022), is that the latter uses a different implementation of the VoF method.…”
Section: Introductionmentioning
confidence: 99%